Youth and children's tourism: the essence and classification by age - Мельнійчук, М. М.; Зейко, В. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
This article is devoted to the study of children’s and youth tourism. In particular, the classification of tourists depending on travelers' age. In practice, there is no jointly determined differentiation of tourist and standard terminology depending on travelers' age in legal acts and scientific literature. Definitions of children’s and youth tourism by scientists from different fields were analyzed and summarized. Setting age limits corresponding to the concept of "youth" and "youth tourism" was separately justified. My own options to determine the definitions of "children's tourism" and "youth tourism" taking into account the previous studies of various scientists, Laws of Ukraine and the current state of the industry were offered.We formulated the following interpretation of children's and youth tourism as a species (forms) of tourism, depending on the tourists' age: "children's tourism is an organized recreational activity for persons under 18 years outside their permanent place of residence and study related to the use of extracurricular time for recreational, educational, cultural, cognitive, local history and sports activities"; "Youth tourism is the recreational activity for young people between the ages of 18 and 35, associated with the cognitive, recreational, sports, cultural and entertaining activities outside the permanent place of residence and study, without the purpose of making a profit at the location."We also set the most important functions of children’s and youth tourism as one of the best methods of teaching and local history work that promote patriotic and cultural education of the younger generation, the ability to enhance their intellectual and cultural level, the development of observation, elimination of physical fatigue, psychological tension and stress.